Histochemical research of cells functionally leading tissue liver and kidneys of rats after intravenous application of nanoparticles magnetite - I. V. Milto; I. V. Sukhodolo; T. K. Klimentiyeva; N. M. Shevtsova (Бюллетень сибирской медицины)
After unitary and repeated intravenous application magnetite is shown their distribution in organism of a rat by method of magnetic resonance imaging. Accumulation of particles in a liver and a spleen of animals is shown. We studied intracellular activity main enzymes of hepatocyte and nephrocyte rats in various periods after intravenous application of nanoparticles magnetite by histochemical method. Intravenous application of magnetite is accompanied change of energetic and plastic metabolism of studied cells.